Sedimentological characterization of Antarctic moraines using UAVs and Structure-from-Motion photogrammetry. Issue 230 (2015) - Westoby, Matthew J.; Dunning, Stuart A.; Woodward, John; Hein, Andrew S.; Marrero, Shasta M.; Winter, Kate; Sugden, David E.
Abstract: In glacial environments particle-size analysis of moraines provides insights into clast origin, transport history, depositional mechanism and processes of reworking. Traditional methods for grain-size classification are labour-intensive, physically intrusive and are limited to patch-scale (1 m 2 ) observation. We develop emerging, high-resolution ground- and unmanned aerial vehicle-based 'Structure-from-Motion' (UAV-SfM) photogrammetry to recover grain-size information across a moraine surface in the Heritage Range, Antarctica. SfM data products were benchmarked against equivalent datasets acquired using terrestrial laser scanning, and were found to be accurate to within 1.7 and 50 mm for patch- and site-scale modelling, respectively. Grain-size distributions were obtained through digital grain classification, or 'photo-sieving', of patch-scale SfM orthoimagery. Photo-sieved distributions were accurate to <2 mm compared to control distributions derived from dry-sieving. A relationship between patch-scale median grain size and the standard deviation of local surface elevations was applied to a site-scale UAV-SfM model to facilitate upscaling and the production of a spatially continuous map of the median grain size across a 0.3 km 2 area of moraine. This highly automated workflow for site-scale sedimentological characterization eliminates much of the subjectivity associated with traditional methods and forms a sound basis for subsequent glaciological process interpretation and analysis.